Cardiometabolic Health Among Adult Offspring of Hypertensive Pregnancies: The Cardiovascular Risk in Young Finns Study. Issue 1 (6th January 2018) - Tapp, Robyn J.; Hughes, Alun D.; Kähönen, Mika; Wong, Tien Yin; Witt, Nicholas; Lehtimäki, Terho; Hutri‐Kähönen, Nina; Sahota, Pinki; Juonala, Markus; Raitakari, Olli T.
Abstract : Background: Cardiometabolic health among adult offspring of hypertensive disorders of pregnancy (HDP) is relatively unknown. We hypothesized that offspring of HDP would have abnormalities in the retinal microvasculature and cardiac structure by midadulthood. Methods and Results: The Cardiovascular Risk in Young Finns Study included randomly selected children from 5 Finnish university cities. The mean age of participants was 40 years (range 34–49 years) at the time of retinal photography and cardiac assessment. Offspring born ≥37 weeks of gestation and appropriate for gestational age (n=1006) were included. Offspring of HDP had higher systolic blood pressure (β=4.68, P <0.001), body mass index (β=1.25, P =0.009), and waist circumference (β=0.25, P =0.042), compared with offspring of normotensive pregnancies. However, no differences in fasting glucose, insulin, lipid profile, carotid intima media thickness, or brachial artery flow‐mediated dilatation were shown. Retinal arteriolar diameters were narrower (β=−0.43, P =0.009) and longer (β=32.5, P =0.023) and the arteriolar length‐to‐diameter ratio was higher (β=2.32, P =0.006) among offspring of HDP, after adjustment for age and sex. Left atrial volume indexed to body surface area (β=1.34, P =0.040) was increased. Adjustment for the confounding effects of birth weight, body mass index, smoking and socioeconomic status, and the mediating effect of hypertension had little impact on the associations. Conclusions: Abnormalities of the retinal microvasculature and cardiac structure are seen in offspring of HDP in midadulthood. These findings may need to be considered in future primary prevention strategies of cardiovascular disease among offspring of HDP.